PENGARUH PENGGUNAAN MEDIA KARTU BERGAMBAR MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE NHT TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA - Nur Apriyani; Tri Jalmo; Rini Rita Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
Based on observation and interview with biology teacher  students critical thinking skill were not optimally developed yet. The experiment aims to find out the influence of applying pictured card media through NHT cooperative learning model  towards improvement of students critical thinking skill. This  quasi experiment study used  pretest posttest group non equivalent designed. Sample in this experiment are students from X2 and X4  class which obtained from population by cluster random sampling tehnique. Quantitative data  was obtained from   pretest and posttest scores which statistically analyzed with t-test using SPSS version 17 in 95% confidence levels. Qualitative data are student’s learning activities and students responses about applying  pictured card media through cooperative learning model type NHT which descriptively analyzed. Result of this study showed that the average of students critical thinking skill  improve significantly ( eksperimen class="70",64 control = 33,44). The average of student learning activities percentage in all observed aspects in experimental class showed  increased significantly  (eksperimen = 81,69% kontrol = 67,51%). The students (90,09%) also gives positive responses in appyling pictured card media through  NHT cooperative learning model. Keywords:  picture card media,, cooperative learning of NHT critical thinking skill, protista